The new transnational activism - Tarrow, Sidney G. (Cambridge studies in contentious politics., 2005)
"The New Transnational Activism is a study that follows the paths of transnational activists through a variety of processes between the local and the global. From labor organizers to immigrant activists, from environmentalists to human rights campaigners, from global justice protesters to Islamist militants, it shows how ordinary people gain new perspectives, experiment with new forms of action, and sometimes emerge with new identities through their contacts across boarders. The book asks how and to what extent transnational activism changes domestic actors, their forms of claims making, and their prevailing strategies."--Jacket